2003
DOI: 10.1128/jvi.77.19.10479-10487.2003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Replicating Capacity of a Chimeric Poliovirus That Carries the Internal Ribosome Entry Site of Hepatitis C Virus in a New Mouse Model Transgenic for the Human Poliovirus Receptor

Abstract: Nucleotides (nt) 108 to 742 of an infectious cDNA clone of poliovirus (PV) Mahoney strain, including the corresponding region of the internal ribosome entry site (IRES), was replaced by nt 28 to 710 of hepatitis C virus (HCV) cDNA corresponding to the whole HCV IRES. A chimeric PV (2A-369) was generated by transfecting mammalian cells with an RNA transcribed in vitro from the cDNA. To examine replicating capacity of virus 2A-369 in the brain and liver of a mouse model for poliomyelitis, a new mouse model (MPVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
(29 reference statements)
2
26
0
Order By: Relevance
“…Previously, poliovirus dependent on the HCV IRES was reported to be cleared from the brain and spinal cord of adult mice without causing disease (13). These results led to the conclusion that the HCV IRES does not mediate translation initiation in the murine brain and spinal cord.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Previously, poliovirus dependent on the HCV IRES was reported to be cleared from the brain and spinal cord of adult mice without causing disease (13). These results led to the conclusion that the HCV IRES does not mediate translation initiation in the murine brain and spinal cord.…”
Section: Discussionmentioning
confidence: 59%
“…Viral replication could be regulated by organ-specific synthesis, localization, or modification of these cell proteins. Recombinant polioviruses dependent on the IRES of human rhinovirus 2 or hepatitis C virus (HCV) do not accumulate or cause disease in the brain and spinal cord of mice (12,13,20). These results have been interpreted as indicating that the IRESs of rhinovirus and HCV do not mediate translation initiation in the brain and spinal cord.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Additional studies confirmed the validity of these findings following inoculation of cynomolgus monkeys and suggested that interactions between specific stem-loop structures (V and VI) within the poliovirus IRES are a major determinant of neurovirulence in addition to the known attenuating lesion in stem-loop V (22). Recently, Nomoto and colleagues reported altered tissuespecific viral replication (in the transgenic mouse model) of a chimeric poliovirus that contains the IRES sequences from hepatitis C virus (HCV), further emphasizing the importance of these RNA sequences in poliovirus tropism and attenuation (23).…”
Section: Figurementioning
confidence: 99%
“…It has been suggested that poliovirus tropism, defined as the organs where the virus replicates, is determined by cell type-specific differences in translation initiation by the poliovirus IRES (11)(12)(13)(14). Poliovirus replication is limited to the brain and spinal cord, oropharyngeal and intestinal mucosa, tonsils, Peyer's patches, and cervical and mesenteric lymph nodes (15).…”
Section: Introductionmentioning
confidence: 99%